2021
DOI: 10.3390/healthcare9091132
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: Origin, Intermediate Host and Allergenicity Features and Hypotheses

Abstract: The goal of this study is to investigate the probable intermediate hosts and the allergenicity of the notorious virus SARS-CoV-2 to understand how this virus emerged. The phylogenetic analysis of the virus spike proteins indicates that SARS-CoV-2 falls into various small subclades that include a bat coronavirus RaTG13, suggesting bats as a likely natural origin. Refined alignment of the spike protein in NCBI found several fragments that are specific to SARS-CoV-2 and/or SARS-CoV are specific to Rattus norvegic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
(87 reference statements)
2
9
0
Order By: Relevance
“…SARS-CoV-1 (Betacoronavirus lineage B) and MERS-CoV (Betacoronavirus lineage C) are known to be enzoonotic in bats and other species such as civets or camels with occasional spillovers into human populations (63,68). Similarly, SARS-CoV-2 (Betacoronavirus lineage B) has most likely been transmitted zoonotically from bats (69)(70)(71)(72)(73)(74). Given that bats are a frequent source of dangerous viruses, we also tested the bat coronavirus HKU9-M pro (Betacoronavirus lineage D) (6,75).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-1 (Betacoronavirus lineage B) and MERS-CoV (Betacoronavirus lineage C) are known to be enzoonotic in bats and other species such as civets or camels with occasional spillovers into human populations (63,68). Similarly, SARS-CoV-2 (Betacoronavirus lineage B) has most likely been transmitted zoonotically from bats (69)(70)(71)(72)(73)(74). Given that bats are a frequent source of dangerous viruses, we also tested the bat coronavirus HKU9-M pro (Betacoronavirus lineage D) (6,75).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that rats might be potential intermediate reservoirs of SARS-CoV-2. A recent study also proposed that rodents are the intermediate reservoirs of SARS-CoV-2 and SARS-CoV ( 23 ). To determine the potential prevalence of SARS-CoV-2 in rats, further serology and molecular surveillance of SARS-CoV-2 variants in domestic rats and wild rats should be performed in regions where B.1.351 and other variants circulate.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to the limitations of virus metagenomics technology that we cannot thoroughly know the diversity and richness of viruses that are carried by host animals. However, some studies have shown that rodents may serve as intermediate hosts of the coronavirus [75], which suggests that we need to further explore the complex viral ecosphere among virus hosts and discover the source and mode of transmission of zoonotic viruses.…”
Section: Discussionmentioning
confidence: 99%